CLINICAL INVESTIGATION OF BACAMPICILLIN FOR TREATING URINARY TRACT INFECTION - HAMANO, KOICHIRO; TOCHIGI, HIROMI; TADA, SHIGERU (CHEMOTHERAPY, 1979)
1) We treated following 48 cases of urinary tract infection by Bacampicillin (BAPC). 11 cases of male and 37 cases of female, from 16 years till 68 years old. 27 cues of simple cystitis, 2 cues of simple pyelonephritis, 11 cases of complicated cystitis and 8 cases of complicated pyelonephritis. 2) Clinical efficacy judged by the Evaluation Criteria for Urinary Tract Infection was 82.3% in simple UTI cases, 57.9% in complicated UTI cases and 72.9% in total cases. 3) E. coil, Staph. epidermidis and Staph. aureus were sensitive to BAPC. This fact was also proved by the clinical evidence. 4) Good clinical response was obtained in complicated UTI by BAPC. This was probably due to its high absorption rate and high urinary excretion rate. 5) No abnormal findings in hematology and blood chemistry. 6) One vomiting and one anorexia were observed during BAPC therapy. 7) BAPC was considered an excellent drug for treating urinary tract infection.